Development of a method for determining the size of clearance in sliding bearings - Žegarac, Nikola P. (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The purpose of this paper is to present the importance of applying a new diagnostic method with a monitoring system and its capability to reliably determine when and where the problem will occur related to the wear of plain bearings in further operation of the plant, to offer a quality assessment of how the system will continue to function over time, to predict causes of failures and how to eliminate them as well as to provide time for planned maintenance of technical systems. Method:The new method solves the problem of sliding bearing diagnostics by measuring the dynamic trajectories (orbit) of the sleeve in the sliding bearing. Modern methods of technical diagnostics based on the measurement of dynamic parameters and electrical quantities and their analysis enable the support of measuring systems and measurement sensors from different manufacturers. Results: Measurements of the dynamic trajectories of sleeves in sliding bearings determine the values characterizing: normal condition, initial clearance size, further clearance increase, bearing clearance sizes, the moment when the state parameters are close to the upper limit of the allowable clearance, and the specific clearance size when further plant exploitation can cause system failure. Conclusion: The new diagnostic method and monitoring systems can be widely applied in all technical fields: internal combustion engines, hydroelectric power plants, thermal power plants, process plants, and in many other areas. Many monitoring systems, compatibility of devices and equipment of different manufacturers are supported by hardware and software. The calculations of theoretical and experimental dynamic parameters were verified. The method has a wide range of possibilities of application.